Adverse childhood experiences among a treatment‐seeking sample of adults with eating disorders. (9th January 2022) - Rienecke, Renee D.; Johnson, Craig; Mehler, Philip S.; Le Grange, Daniel; Manwaring, Jamie; Duffy, Alan; McClanahan, Susan; Blalock, Dan V.
Abstract: Objective: The purpose of the current study was to examine the prevalence of adverse childhood experiences (ACEs) among adults with eating disorders (EDs), to assess whether experiencing a greater number of ACEs is associated with more severe ED psychopathology, and to determine whether ACEs predict treatment outcome. Method: Participants were 1819 patients (88.5% female, ages 18–72) admitted to one of two treatment facilities at inpatient, residential, or partial hospitalisation levels of care. The Adverse Childhood Experiences Survey and the Eating Pathology Symptom Inventory (EPSI) were completed at admission and the EPSI at discharge. Results: Female patients reported higher ACEs than males ( p  = 0.03), and all diagnoses except avoidant/restrictive food intake disorder had significantly higher ACEs than patients with anorexia nervosa‐restricting type (AN‐R) ( p 's < 0.01). Across diagnoses, higher ACEs were associated with decreases in binge eating scores during treatment, but were not associated with changes in purging or restricting. Within diagnoses, higher ACEs scores were associated with decreases in purging for patients with AN‐R and increases in purging for patients with binge eating disorder. Conclusions: Results partially supported the hypothesis that higher ACEs would be associated with more severe ED psychopathology. Highlights: Adverse childhood experiences (ACEs) have been found to be associated with a number of mental health disorders and unhealthy behaviours in adulthood The purpose of the current study is to examine the prevalence of ACEs in a sample of adults with eating disorders (EDs), to assess whether experiencing a greater number of ACEs is associated with more severe ED psychopathology, and to determine whether ACEs predict treatment outcome Female patients reported higher ACEs than male patients, and across diagnoses, higher ACEs were associated with decreases in binge eating scores during treatment, but were not associated with changes in the Eating Pathology Symptom Inventory purge or restrict subscales